Optimization of oil palm fronds conversion to Levulinic Acid using Fe/HY Zeolite Catalyst - Nur Aainaa Syahirah Ramli; Nor Aishah Saidina Amin (Universiti Kebangsaan Malaysia, 2015)
Levulinic acid (LA) is a versatile platform chemical with numerous potential uses. Conversion of oil palm fronds (OPF) to LA over Fe/HY zeolite catalyst has been conducted in this study. The optimization process using Box-Behnken design gave 19.6% of LA yield at 181.7°C reaction temperature, 7.7 h reaction time, 1.13 g Fe/HY zeolite loading and 0.25 g OPF loading. The efficiency of OPF conversion at the optimum conditions was determined to be 61.1%. It was also demonstrated that Fe/HY zeolite gave sufficient performance for five successive cycles of OPF conversion to LA. The results suggested that Fe/HY zeolite is potential as catalyst for biomass conversion to LA.